2019
DOI: 10.3389/fnmol.2019.00206
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Retinal Ca2+/Calmodulin-Dependent Kinase II-β (CaMKII-β) at Bipolar Cell Gap Junctions and Cross-Reactivity of a Monoclonal Anti-CaMKII-β Antibody With Connexin36

Abstract: Neuronal gap junctions formed by connexin36 (Cx36) and chemical synapses share striking similarities in terms of plasticity. Ca 2+ /calmodulin-dependent protein kinase II (CaMKII), an enzyme known to induce memory formation at chemical synapses, has recently been described to potentiate electrical coupling in the retina and several other brain areas via phosphorylation of Cx36. The contribution of individual CaMKII isoforms to this process, however, remains unknown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The expression of CaMKII in the retina has been studied in rodents, where it was found in somas of the inner nuclear layer and ganglion cell layer as well as in their processes in the inner plexiform layer (Bronstein et al., 1988; Ochiishi et al., 1994; Tetenborg et al., 2017; Tetenborg et al., 2019). These studies showed that the alpha isoform is expressed by starburst amacrine cells in addition to ganglion cells and other amacrine cells cell types (Ochiishi et al., 1994; Tetenborg et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of CaMKII in the retina has been studied in rodents, where it was found in somas of the inner nuclear layer and ganglion cell layer as well as in their processes in the inner plexiform layer (Bronstein et al., 1988; Ochiishi et al., 1994; Tetenborg et al., 2017; Tetenborg et al., 2019). These studies showed that the alpha isoform is expressed by starburst amacrine cells in addition to ganglion cells and other amacrine cells cell types (Ochiishi et al., 1994; Tetenborg et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The beta and delta isoforms are located at bipolar axon terminals where they are differentially coexpressed with gap junction forming connexins (Tetenborg et al., 2017). The beta isoform has been suggested to play a role in the modulation of electrical synapses (Tetenborg et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Camk2 isoforms are widely expressed in the retina and recently have been found to mediate the angiogenic actions of a range of growth factors in human retinal endothelial cells ( Ashraf et al, 2019 ). CAM2KA, in particular, is an enzyme known to induce memory formation at chemical synapses and has been described to potentiate electrical coupling in the retina ( Tetenborg et al, 2019 ). According to Tetenborg et al (2017) , Camk2a is strongly expressed in starburst ACs, and in a few other cell types ( Tetenborg et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the major neuronal isoform CaMKII showed virtually no association with Cx36, while the neuronal isoform CaMKII and the widespread isoform CaMKII were associated with Cx36 gap junctions in a somewhat cell-type selective manner (Tetenborg et al, 2017;Tetenborg et al, 2019). In AII amacrine cells, in which the CaMKII-driven potentiation of Cx36 coupling depends on Cx36 phosphorylation (Kothmann et al, 2012), CaMKII was the major isoform present (Tetenborg et al, 2017).…”
Section: Discussionmentioning
confidence: 99%